先化简再求值(a-2b)(3a-2b)-3(a-b)(a+3b),其中a=-(1/2),b=1
人气:227 ℃ 时间:2020-02-05 20:16:12
解答
(a-2b)(3a-2b)-3(a-b)(a+3b)
=3a²-2ab-6ab+4b²-3(a²+3ab-ab-3b²)
=3a²-8ab+4b²-3(a²+2ab-3b²)
=3a²-8ab+4b²-3a²-6ab+9b²
=13b²-14ab
=b(13b-14a)
=1X(13X1-14X(-1/2))
=13+7
=20
推荐
- 化简求值(-3a^2b)^3-8(a^2)^2×(-b)^2×(-a^2b),其中a=1,b=-1
- 先化简,再求值:(a-b)(a-2b)-(3a-2b)(a-3b),其中a=4,b=-1
- 2b+3b-3a-5b+3,其中a=-1.b=2,先化简,再求值
- 先化简,后求值:[(a-3b)∧2+(3a+b)∧2](a+b)(2a-2b),其中(a+2)∧2+b-1=0
- 先化简,再求值:(-3a^2b)^3-8(a^2)^2*(-b)^2*(-a^2b),其中a=1,b=-1
- 作文 A day at school (不少于6句,根据问题和提示)
- 2/9+3/4=5/9x 解方程
- 英语翻译
猜你喜欢